PERLINDUNGAN HUKUM PEMEGANG SAHAM MINORITAS DALAM PEMBAGIAN HARTA PAILIT PERUSAHAAN TERBUKA: ANALISIS PROBLEMATIKA DAN MODEL REGULASI IDEAL DI INDONESIA - Sudirman, M.; Guritno, Yulianto; Sungkawa Putra, Andri Jatnika; Abdurahman, Abdurahman (Gapenas Publisher, 2025)
Legal protection for minority shareholders in the bankruptcy of public companies in Indonesia faces significant challenges due to existing regulatory limitations. This research aims to analyze the problematic aspects of minority shareholder protection in the distribution of bankrupt assets under Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and Law No. 40 of 2007 concerning Limited Liability Companies, while simultaneously formulating an ideal regulatory model and mechanisms to strengthen such protection. Employing a normative legal research method with a conceptual and comparative analytical approach, this study finds that minority shareholders are at the lowest priority in the distribution of bankrupt assets, leading to substantial capital loss and high legal uncertainty due given their status as capital owners rather than creditors. The absence of specific provisions in the Bankruptcy Law and the limitations of the Company Law exacerbate this vulnerability. Therefore, the ideal regulatory model proposes reforming the payment hierarchy by introducing a quasi-creditor status for public shareholders, strengthening corporate governance and minority information rights, and expanding the role of the Financial Services Authority (OJK) in early oversight and restructuring facilitation. The implication of this research is the urgency of legislative reform to create a more equitable and comprehensive legal framework to maintain minority shareholders confidence in the Indonesian capital market.